Effects of two semen extenders on motility and integrity of sperm membrane in ovine frozen semen - Cabrera V., Próspero (2010)
The objective of the study was to evaluate the effects of two semen extenders: Tris- Fructose-egg yolk (Tris) and Citrate-Glucose-egg yolk (citrate) on motility and sperm membrane integrity (HOST) in ovine frozen semen in pellets. The study was carried out at the Semen Bank of the Agrarian University La Molina, in Lima, Peru, using 4 rams (2 Assaf and 2 Blackbelly) of 3.5 to 4 years old. A covariance analysis was used to evaluate the effect of the treatment and breed on Individual Progressive Motility (IPM), and randomized block design to evaluate the effect of extenders on sperm membrane integrity. Semen was frozen of dry ice and thawing was done in test tubes at 38 °C. In the Assaf breed, IPM of thawed semen was 63.77 and 61.11% when using Tris and citrate respectively, showing statistical difference (p<0.05). In the Blackbelly breed the IPM was 62.33 and 61.33%, when used Tris and citrate respectively, and without significant difference. In the Assaf the HOST values of thawed semen were 43.56 and 40.38%, while in Blackbelly were 40.19 and 38.16% respectively, both without significant differences. It is concluded that Tris showed better effect on individual motility but both of them had similar effect on sperm membrane integrity.